1998
DOI: 10.1080/00029157.1998.10404199
|View full text |Cite
|
Sign up to set email alerts
|

Wart Regression in Children: Comparison of Relaxation-Imagery to Topical Treatment and Equal Time Interventions

Abstract: Relaxation mental imagery (RMI), standard topical treatment (TopTx), and equal time-control interventions were compared on measures of wart regression in sixty one, 6–12-year-old children. Subjects chose one common (“index”) wart and attended 4 visits over 8 weeks. At each visit, total and “index” extremity wart number were counted and a photo was taken of the “index wart” for later measurement. On average, total wart number decreased by 10% and “index wart” area decreased by 20% with no significant gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…For example, in the study by Felt et al. , 29 there were 10 patients cured out of 17 patients taking SA therapy and five patients cured out of 20 patients taking placebo that completed the trial. This is equivalent to a risk ratio (RR) of 2·35 (95% CI 1·00–5·54), which is of borderline significance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the study by Felt et al. , 29 there were 10 patients cured out of 17 patients taking SA therapy and five patients cured out of 20 patients taking placebo that completed the trial. This is equivalent to a risk ratio (RR) of 2·35 (95% CI 1·00–5·54), which is of borderline significance.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to previous reviews, we set out to extract and analyse data using ITT principles wherever possible, as this methodology is the highest quality form of analysis that can be undertaken. Our search results yielded 77 relevant studies as outlined below 9–80 …”
mentioning
confidence: 99%
“…Reports by Bloch (24) and Sulzberger and Wolf (25) on the efficacy of suggestion in treating verruca vulgaris have since been confirmed numerous times to a greater or lesser degree (69–72), but have failed to be confirmed in a few studies (73,74). A recent study that showed negative results was criticized for using a negative suggestion of not feeding the warts rather than a positive suggestion about having the warts resolve (75). Many reports confirm the efficacy of hypnosis in treating warts (76–91).…”
Section: Medical Hypnotherapy For Treating Specific Dermatologic Condmentioning
confidence: 94%
“…For treatment of juvenile warts, hypnosis is at least as effective as topical treatment and associated with fewer relapses. 10 Hypnosis is valuable as an adjunctive intervention during painful procedures, [11][12][13] and many adults and children use self-hypnosis to teach themselves to be HELPING CHILDREN AND ADULTS WITH HYPNOSIS AND BIOFEEDBACK comfortable through procedures without any pharmacologic treatment. 14 Training in self-hypnosis is a valuable adjunct for both children and adults with chronic illnesses such as cancer, cardiac failure, asthma, hemophilia, sickle cell disease, and arthritis.…”
Section: ■ a Wide Range Of Therapeutic Applicationsmentioning
confidence: 99%